2017
DOI: 10.1111/1346-8138.13956
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib for the treatment of moderate to severe chronic plaque psoriasis in Japanese patients: Subgroup analyses from a randomized, placebo‐controlled phase 3 trial

Abstract: Tofacitinib is an oral Janus kinase inhibitor. These post‐hoc analyses assessed tofacitinib efficacy and safety in Japanese patients with psoriasis enrolled in a 52‐week global phase 3 study. Patients received tofacitinib 5 mg, tofacitinib 10 mg or placebo twice daily (b.i.d.); placebo‐treated patients advanced to tofacitinib at week 16. Primary efficacy end‐points were the proportions of patients with 75% or more reduction from baseline Psoriasis Area and Severity Index (PASI‐75) and Physician's Global Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…Tofacitinib 10 mg was found to be non-inferior to etanercept, but tofacitinib 5 mg was not shown to be non-inferior to etanercept. 32 Although study results demonstrated that both the 5 mg and 10 mg doses were effective in treating plaque psoriasis, [33][34][35] the 10 mg dose was proven to be more efficacious. 36 However, this higher dose is associated with increased safety concerns, leading the FDA to decline approval of tofacitinib for moderate-to-severe plaque psoriasis.…”
Section: Psoriasis Clinical Trialsmentioning
confidence: 99%
“…Tofacitinib 10 mg was found to be non-inferior to etanercept, but tofacitinib 5 mg was not shown to be non-inferior to etanercept. 32 Although study results demonstrated that both the 5 mg and 10 mg doses were effective in treating plaque psoriasis, [33][34][35] the 10 mg dose was proven to be more efficacious. 36 However, this higher dose is associated with increased safety concerns, leading the FDA to decline approval of tofacitinib for moderate-to-severe plaque psoriasis.…”
Section: Psoriasis Clinical Trialsmentioning
confidence: 99%
“…NAPSI scores continued to decrease through week 52 in both tofacitinib dose groups. By week 52, 22.2 and 47.6% of the patients who received tofacitinib 5 and 10 mg, respectively, achieved NAPSI 75 [19]. Adverse events most commonly related to laboratory parameter abnormalities were noted.…”
Section: Tofacitinibmentioning
confidence: 94%
“…На 16-й нед. значительно больше пациентов, получавших тофацитиниб по сравнению с плацебо, достигли NAPSI 50 (32,8,44,2 против 12,0%), NAPSI 75 (16,9, 28,1 против 6,8%) [30,31].…”
Section: лечение «малыми» молекулами и биологическими препаратамиunclassified